2018
DOI: 10.1155/2018/3752723
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review of Women’s Sex Hormone Changes by Acupuncture Treatment: Analysis of Human and Animal Studies

Abstract: Background It has been known that acupuncture treatment relieves gynecological disorders such as menopause, ovarian dysfunction, and dysmenorrhea. Sex hormones, including estrogen, progesterone, and gonadotropins, are related to the women disease. However, regulative effect of acupuncture on sex hormones has not been fully identified. Methods Acupuncture articles including analysis of sex hormones were searched in electronic databases from inception to June 2018. The methodological quality was assessed using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Tibial nerve stimulation in the neuromodulation field primarily focuses on pelvic organs such as the bladder or bowel, with limited literature on the reproductive tract. In contrast, electro-acupuncture studies primarily focus on stimulating the “SP6” acupoint alone or in conjunction with other acupoints to treat hormone-associated disorders such as menopause [38], primary dysmenorrhea (menstrual cramps) [39, 40] and labor [41–43]. However, electro-acupuncture has also been indicated in the treatment of urinary (overactive bladder [44], stress urinary incontinence [45]) or GI disease (fecal incontinence [46]).…”
Section: Discussionmentioning
confidence: 99%
“…Tibial nerve stimulation in the neuromodulation field primarily focuses on pelvic organs such as the bladder or bowel, with limited literature on the reproductive tract. In contrast, electro-acupuncture studies primarily focus on stimulating the “SP6” acupoint alone or in conjunction with other acupoints to treat hormone-associated disorders such as menopause [38], primary dysmenorrhea (menstrual cramps) [39, 40] and labor [41–43]. However, electro-acupuncture has also been indicated in the treatment of urinary (overactive bladder [44], stress urinary incontinence [45]) or GI disease (fecal incontinence [46]).…”
Section: Discussionmentioning
confidence: 99%
“…Old cows have no menopause at the time of slaughter 16 , 17 . In a recent literature review of 23 selected previous papers 18 , blood FSH concentration in human females approaching menopause decreased in 21 studies, while the remaining two reported an increase. However, it is possible that other factors, besides EPl (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that other factors, besides EPl (e.g. oestradiol and prolactin), may contribute to controlling blood FSH levels in older human females 18 . In conclusion, our findings indicated that age-related qualitative and quantitative differences in brain EPl may be crucially involved in age-related infertility in cows.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are few studies on the effects of acupuncture on children's sexual development and secondary sexual signs, there are relevant clinical and basic researches on the effects of acupuncture on adult women's reproductive endocrine function [19,20]; literature studies have shown that acupuncture treatment can reduce the serum FSH and LH levels of adult women, improve the E2 level of women, and improve menstrual cycle and ovarian function [21,22]; acupuncture has been applied to primary ovarian dysfunction [23], polycystic ovarian syndrome [24], [25], dysmenorrhea [26], and other female reproductive endocrine-related diseases. Although the mechanism of acupuncture on female reproductive endocrine system is not very clear at present, it has been found that acupuncture can regulate some neurotransmitters and neuropeptides, such as β-endorphin, dopamine, and prostaglandin [27][28][29] and then affect the hypothalamic pituitary gonadal axis, thus regulating the level of serum sex hormones [30].…”
Section: Discussionmentioning
confidence: 99%